Comparison of micronuclei frequency in bone marrow cells of three rat lines - Arencibia-Arrebola, D.F.; Rosario-Fernandez, L.A.; Suarez-Fernandez, Y.E.; Vidal-Novoa, A. (Цитология и генетика, 2013)
The aim of this paper is to compare the spontaneous and induced with cyclophosphamide micronucleus indexes in bone marrow cells of the Sprague Dawley, Lewis and Wistar rat lines. Five experimental groups were formed (10 animals of each sex and of each line, in every group). The first group was used as the negative control (intact animals), the second one was exposed to oral administration of drugs; other conditions were the same as for the other groups. The third group was treated with 2 % Tween 65 and the fourth group was treated with 0.9 % NaCl. Both substances were administered by oral way to 2 ml/kg during 14 days. The fifth group was treated intraperitoneally with strong mutagen cyclophosphamide in the dose of 50 mg/kg (10 ml/kg in solution), on 48th and 24th hours before euthanasia. The Sprague Dawley line (both sexes) was significantly different from the other lines. Rats of this line had lower index of spontaneous formation of micronuclei, higher index of cyclophosphamideinduced micronucle formation, percent of micronucleated erythrocytes in bone marrow and the index of cytotoxicity. The results obtained make it possible to identify the most appropriate line of rats as model animals for studies of genotoxicity. It will allow also to obtain more accurate estimates of genotoxicity of various substances. Сравнивали спонтанные и индуцированные циклофосфамидом микроядерные индексы в клетках костного мозга трех линий крыс – Sprague Dawley, Льюис и Вистар. Сформировали пять экспериментальных групп (по 10 животных каждого пола и линии в каждой группе). Первую группу использовали в качестве негативного контроля (интактные животные), вторая служила контролем влияния перорального приема препаратов. Все условия содержания были одинаковыми для всех групп животных. Крыс третьей группы обрабатывали 2 % Tween 65, а четвертой группы – 0,9 % NaCl. Оба вещества вводили перорально в дозе 2 мл/кг в течение 14 дней. Животных пятой группы обрабатывали внутрибрюшинно циклофосфамидом в дозе 50 мг/кг (10 мл/кг раствора), за 48 и 24 ч до эвтаназии. Линия Sprague Dawley (оба пола) существенно отличается от других. Крысы этой линии имели низкие показатели спонтанного образования микроядер и высокий индекс при индукции циклофосфамидом, а также процент эритроцитов с микроядрами в костном мозге и индекс цитотоксичности. Полученные результаты позволяют определить наиболее подходящие линии крыс в качестве модельных животных для изучения генотоксичности. Это также позволит получать более точные оценки генотоксичности различных веществ. Порівнювали спонтанні та індуковані циклофосфамідом мікроядерні індекси в клітинах кісткового мозку трьох ліній щурів – Sprague Dawley, Люіс і Вистар. Сформували п’ять експериментальних груп (по 10 тварин кожної статі і лінії в кожній групі). Першу групу використали як негативний контроль (інтактні тварини), друга слугувала контролем впливу перорального прийому препаратів. Всі умови утримання були однаковими для всіх груп тварин. Щурів третьої групи обробляли 2 % Тween 65, а четвертої групи – 0,9 % NaCl. Обидві речовини вводили перорально в дозі 2 мл/кг впродовж 14 днів. Тварин п’ятої групи обробляли внутрішньочеревно циклофосфамідом в дозі 50 мг/кг (10 мл/кг розчину), за 48 і 24 год до евтаназії. Лінія Sprague Dawley (обидві статі) істотно відрізнялась від інших. Щури цієї лінії мали низькі показники спонтанного утворення мікроядер і високий індекс при індукції циклофосфамідом, а також відсоток еритроцитів з мікроядрами в кістковому мозку та індекс цитотоксичності. Отримані результати дозволяють визначити найбільш відповідні лінії щурів як модельних тварин для вивчення генотоксичності. Це також дозволить отримувати точніші оцінки генотоксичності різних речовин.